Navigating gender dynamics: a male researcher's experiences on conducting feminist HCI research - Ahmadi, Michael (Frontiers in Human Dynamics, 2023)
In this perspective article, I invite readers to accompany me on a personal journey of self-discovery and transformation as a male researcher within the field of feminist Human-Computer Interaction (HCI). I will delve into the specific topic of gender-opposite research in socio-technical environments and reflect on my experiences, especially the associated challenges and opportunities. My journey exposed me to critical literature and engaged me in long-term fieldwork simultaneously, expanding my understanding of the dynamics that shape our society. My perspectives, sensitization, and awareness of gender-related issues evolved significantly over the course of more than three years of being dedicated to a feminist research project. By sharing this narrative, I hope to promote critical discussions about the significance of both, personal growth, and transformation as well as the need for reflexivity in the pursuit of feminist research (with a focus on the specific context of gender-opposite research in socio-technical environments). I will dive into the complexities that I encountered in the settings and compromises I felt obliged to make which were influenced by the embodied nature of my research. As I will furthermore show, there had been an impact on my research practices in terms of planning, observation, analysis, and writing.